Financial Factors Shaping Stock Prices: Evidence from Food and Beverage Companies (2016-2020): Faktor Finansial yang Membentuk Harga Saham: Bukti dari Perusahaan Makanan dan Minuman (2016-2020) - Vionita, Silvia Al; Setiyono, Wisnu Panggah (Indonesian Journal of Law and Economics Review, 2023)
This research employs quantitative methods and secondary data analysis to investigate the relationship between financial variables and stock prices in the food and beverage industry. Utilizing a purposive sampling method, 50 samples from 10 food and beverage companies listed on the IDX are examined over a five-year period. The study reveals that Net Profit Margin and Capital Structure both exert a positive and significant influence on stock prices, whereas Profitability demonstrates a significant negative impact. Notably, when considered together, these three variables collectively influence stock prices. This study's findings have implications for investors, financial analysts, and policymakers, offering insights into the complex interplay between financial metrics and stock market performance within the food and beverage sector. Highlights: Financial Metrics Impact: Net Profit Margin and Capital Structure positively influence stock prices, while Profitability has a negative impact. Sector-Specific Insights: The study focuses on the food and beverage industry, offering sector-specific implications for stakeholders. Methodological Approach: Quantitative analysis using secondary data and multiple linear analysis techniques informs the research findings. Keywords: Stock Prices, Financial Factors, Food and Beverage Industry, Secondary Data Analysis, Multiple Linear Analysis.